Distributed Computing and Networking 12th International Conference, ICDCN 2011, Bangalore, India, January 2-5, 2011. Proceedings - Aguilera, Marcos K.; Yu, Haifeng; Vaidya, Nitin H.; Srinivasan, Vikram; Choudhury, Romit Roy.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 12th International Conference on Distributed Computing and Networking, ICDCN 2011, held in Bangalore, India, during January 2-5, 2011. The 31 revised full papers and 3 revised short papers presented together with 3 invited lectures were carefully reviewed and selected from 140 submissions. The papers address all current issues in the field of distributed computing and networking. Being a leading forum for researchers and practitioners to exchange ideas and share best practices, ICDCN also serves as a forum for PhD students to share their research ideas and get quality feedback from the well-renowned experts in the field.
Keywords: Computer science; Computer Communication Networks; Software engineering; Data protection; Computer software; Information systems; Computer Science; Computer Communication Networks; Programming Techniques; Software Engineering; Systems and Data Security; Algorithm Analysis and Problem Complexity; Information Systems Applications (incl.Internet).